Clinical outcomes following prenatal diagnosis of asymmetric ventriculomegaly, interhemispheric cyst, and callosal dysgenesis (AVID). (21st December 2018) - Oh, Karen Y.; Gibson, Thomas J.; Pinter, Joseph D.; Pettersson, David; Shaffer, Brian L.; Selden, Nathan R.; Sohaey, Roya
Abstract : What's already known about this topic? Fetal ventriculomegaly can be isolated or be a component of structural brain anomaly. Prenatal counseling can be challenging given the variable clinical outcomes associated with fetal ventriculomegaly. When fetal ventriculomegaly is associated with a structural anomaly such as a callosal malformation, postnatal outcomes are worse than for isolated ventriculomegaly. What does this study add? When severe asymmetric ventriculomegaly is identified, an underlying callosal anomaly and midline interhemispheric cyst can be present (AVID triad). Prenatal diagnosis of the AVID triad leads to progressive severe macrocephaly in utero, which often leads to cesarean section delivery. All children in our series with prenatally diagnosed AVID required at least one and in general several neurosurgical procedures, including CSF shunting in all cases. Most of these children had at least moderate to severe motor and language delays, with a wide range of visual deficits, craniofacial abnormalities, and medical comorbidities. Abstract: Objectives: When identified prenatally, the imaging triad of asymmetric ventriculomegaly, interhemispheric cyst, and dysgenesis of the corpus callosum (AVID) can indicate a more serious congenital brain anomaly. In this follow‐up series of 15 fetuses, we present the neurodevelopmental outcomes of a single institution cohort of children diagnosed prenatally with AVID. Methods: Our fetal ultrasound database was queried for cases of AVID between 2000 and 2016. All available fetal MR imaging studies were reviewed for the presence of (a) interhemispheric cysts or ventricular diverticula and (b) dysgenesis or agenesis of the corpus callosum. Clinical records were reviewed for perinatal management, postnatal surgical management, and neurodevelopmental outcomes. Results: Fifteen prenatal cases of AVID were identified. Twelve were live‐born and three pregnancies were terminated. Of the 12 patients, 11 underwent neurosurgical intervention. Of the eight patients surviving past infancy, seven of eight have moderate to severe neurodevelopmental delays or disabilities, encompassing both motor and language skills, and all have variable visual abnormalities. Conclusion: In our cohort of 15 prenatally diagnosed fetuses with AVID, eight survived past infancy and all have neurodevelopmental disabilities, including motor and language deficits, a wide range of visual defects, craniofacial abnormalities, and medical comorbidities.